Peran Koperasi Simpan Pinjam dalam Meningkatkan Perekonomian Masyarakat Studi Kasus Koperasi Bona Mandiri Jaya - Simamora, Eti Damayanti; Perkasa, Ripho Delzy (Ikatan Da'i Indonesia, 2023)
In order to create the implementation of regional autonomy policies, especially in increasing cooperatives, of course, it must empower micro and small businesses which are of particular concern in this use. In line with the existence of regional autonomy policies in the implementation of cooperatives, of course it involves the existence of a property business to determine the quality of the implementation of these cooperatives so that they are able to provide the best competitiveness for the community. The bridal design used in this research is qualitative where the researcher acts as a key instrument in the research supported by data collection techniques using triangulation or combined research